2018
DOI: 10.1186/s13013-018-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Consistent and regular daily wearing improve bracing results: a case-control study

Abstract: BackgroundIn respect to the prescribed regimen and the regular daily pattern, investigate how short-term results are affected by wear time adherence in terms of hours per day.MethodsThis is a case-control study. The setting is outpatient clinic. There were 168 subjects, all of whom met the inclusion criteria: adolescent idiopathic scoliosis and Sforzesco brace prescription of 18 to 23 h/day. The minimum period of follow-up was 4 months, and the maximum was 6 months, which is the average time passing between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 37 publications
0
39
1
Order By: Relevance
“…Patients and their parents’ attitudes towards electronic monitors are significant to the application and popularization of these monitors. Donzelli et al [ 14 ] investigated the attitudes of 364 parents and patients with regards to the use of temperature sensors. They also found that the mean rate of parents stating a completely or at least partially positive attitude was 94.0% while it was 85.6% among patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients and their parents’ attitudes towards electronic monitors are significant to the application and popularization of these monitors. Donzelli et al [ 14 ] investigated the attitudes of 364 parents and patients with regards to the use of temperature sensors. They also found that the mean rate of parents stating a completely or at least partially positive attitude was 94.0% while it was 85.6% among patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common of such devices were temperature and pressure/force sensors. The temperature sensors were proved to be effective to monitor wearing time [2,[10][11][12][13][14][15][16][17][18], but they could not measure the level of wearing tightness. Nicholson et al [10] reported that the mean temperature at the skinbrace interface was 32.8 ± 1.6°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with the TLSO brace has shown to halt rate of progression in idiopathic scoliosis (42,43). The dose-response relation has received much attention recently and it is now generally agreed that the desired effect is better achieved with increased in-brace time (4,43,44).…”
Section: Brace Treatmentmentioning
confidence: 99%